Comparative effects of deficit and partial root‐zone drying irrigation techniques using moderately saline water on ion partitioning in Shiraz and Grenache grapevines. (28th April 2016) - Degaris, K.A.; Walker, R.R.; Loveys, B.R.; Tyerman, S.D.
Abstract: Background and Aims: Deficit irrigation techniques have been used to improve water use efficiency and control vigour in grapevines, but the consequences of using saline water with these techniques have been little investigated. Here, we investigate the effect of deficit irrigation with moderately saline water on within‐vine ion allocation. Methods and Results: Drip‐irrigated own‐rooted Shiraz and Grenache vines grown in pots were subjected to control, reduced control and partial root‐zone drying (both approximately 50% less than control) irrigation treatments utilising moderately saline irrigation (mean of 2.46 dS/m) over two seasons. Plant water status and stomatal conductance were measured during the growing seasons, and at the end of the second season, the vines were destructively sampled to determine plant growth and concentration of ions of various vine structures. When compared against the control, partial root‐zone drying had a higher total concentration of Cl −, Na +, K + and Ca ++ present on a whole vine basis. Although Cl − concentration was elevated in leaves for the partial root‐zone drying treatment, it was partitioned away from leaves on a total content basis relative to both control and reduced control treatments. The partial root‐zone drying treatment also resulted in significantly lower midday leaf water potential. Conclusion: Ion partitioning within grapevines depends on the type of deficit applied. Significance of the Study: Utilising deficit irrigation techniques in combination with saline irrigation water will alter the allocation of ions within a grapevine highlighting the importance of monitoring during the growing season for both fruit composition and long‐term vine health.